2014
DOI: 10.1016/j.hemonc.2014.09.007
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CA mutations in Peruvian patients with HER2-amplified and triple negative non-metastatic breast cancers

Abstract: We found a similar frequency of PIK3CA mutations to that reported in other series. Although we did not include HR+/HER2 patients, those with HER2-amplified tumors were more likely to present PIK3CA mutations compared to patients with triple negative tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 24 publications
(20 reference statements)
3
12
2
1
Order By: Relevance
“…However, targeting HER2 alone was less effective for breast cancer patients with PIK3CA mutations in clinical studies ( 17 , 18 ). In line with these observations, several groups reported that HER2 amplification and mutation of PIK3CA genes could be co-occurring in certain breast cancer population ( 6 , 19 - 22 ). However, the cooperative effect of these two genetic alterations in comparison with either single genetic change on cell oncogenic properties has not been well investigated.…”
Section: Introductionmentioning
confidence: 57%
“…However, targeting HER2 alone was less effective for breast cancer patients with PIK3CA mutations in clinical studies ( 17 , 18 ). In line with these observations, several groups reported that HER2 amplification and mutation of PIK3CA genes could be co-occurring in certain breast cancer population ( 6 , 19 - 22 ). However, the cooperative effect of these two genetic alterations in comparison with either single genetic change on cell oncogenic properties has not been well investigated.…”
Section: Introductionmentioning
confidence: 57%
“…In this study, Silvia et al 53 indicated that TP53 mutations did not predict the NCT response in TNBC patients. Furthermore, analysis of the predictive of PIK3CA mutation on TNBC agents was performed in a biomarker analysis of 81 patients with residual disease after NCT, with finding of PIK3CA mutation not associated with pCR 54.…”
Section: Early Stagementioning
confidence: 99%
“…Mutation p.E542K has been already proved as pathogenic with constitutively activating effect in PI3K/AKT/mTOR signalling pathway in a large number of tumor diseases [28]. In contrast to this well characterized point mutation, the other mutation p.D549N has been described only in a few cases of colorectal carcinoma, breast or endometrial carcinoma so far [29][30][31]. Concerning to its low frequency, the information about its effect in the protein function is still absent.…”
Section: Discussionmentioning
confidence: 99%